44 Primary percutaneous intervention: have we taken our eye off the medicine ball?. (9th June 2011) - Jones, J D; Damm, E; Nijjar, M; Pettit, S; Hawkins, N M; Perry, R
Abstract : Introduction: Primary percutaneous intervention (PPCI) improves survival in patients with ST elevation myocardial infarction (STEMI). Significant resources have been directed to achieving timely reperfusion throughout the UK. However, intensive medical therapy is of equal importance, with landmark clinical trials demonstrating unequivocal morbidity and mortality benefits from β-blockers, angiotensin-converting enzyme inhibitors (ACEI), and angiotensin II receptor blockers (ARB). All trials employed rigorous titration to maximum clinically tolerated doses. We examined whether medical therapy is being applied appropriately in patients referred for PPCI. Methods: Consecutive patients with STEMI referred for PPCI to a large tertiary centre between 1st March and 1st August 2009 were included (n=167). The case records of all patients were reviewed. Myocardial infarction was diagnosed according to standard criteria. Medications and doses on admission, discharge and follow-up were recorded. Contraindications and limits to dose escalation were noted (symptoms, systolic blood pressure <90 mm Hg, heart rate <50 bpm, serum creatinine and potassium). Results: Mean age was 62.0±11.9 years, 72% were male. On discharge, 100% of patients were prescribed clopidogrel, 95.8% aspirin, 98.8% statin, 88.6% β-blockers, and 91.0% ACEI/ARB. However, the inpatient dose of β-blocker or ACEI/ARB was maximum or clinically limited in only 13% and 15% of patients respectively (Abstract 44 figure 1 ). Outpatient follow-up at a mean of 5.0 months was equally concerning. The majority of patients (83%) were neither receiving maximum tolerated doses of β-blocker or ACEI/ARB, nor received instructions to escalate the dose (Abstract 44 figure 2 ). Conclusion: The national service framework and target driven initiatives such as advancing quality promote "tick box" medicine. Quantitative prescribing of secondary prevention is excellent. Qualitative follow-up and titration is not. Whether suboptimal doses convey the mortality benefits observed in landmark clinical trials is unknown. Frameworks to deliver titration of medical therapy must be explored. Options include nurse or pharmacy led services and expansion of cardiac rehabilitation. Reorientation is needed to focus on both quantity and quality.